2006
DOI: 10.1080/13697130500487372
|View full text |Cite
|
Sign up to set email alerts
|

Development of a revised version of the Women's Health Questionnaire

Abstract: Content analysis and evaluation of missing data led to exclusion of 'Menstrual symptoms' and 'Sexual behavior' domains, retaining these as optional modules of the core questionnaire. Additionally, item 13 was excluded because it does not investigate the same concepts as other domains and the deletion of five additional items appeared to improve the questionnaire's factor structure. The revised WHQ comprises 23 items, investigating six domains. The cross-sectional psychometric properties of the 23-item WHQ were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
1
28
0
2
Order By: Relevance
“…Exploratory factor analysis, rather than confirmatory factor analysis, was chosen in this study because analyses of the WHQ on a pooled international database had previously resulted in an unclear factor structure (Girod et al , 2006). Another reason was that the participants in this study reported far more disturbance due to vasomotor episodes compared to the participants used to evaluate the original instrument.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Exploratory factor analysis, rather than confirmatory factor analysis, was chosen in this study because analyses of the WHQ on a pooled international database had previously resulted in an unclear factor structure (Girod et al , 2006). Another reason was that the participants in this study reported far more disturbance due to vasomotor episodes compared to the participants used to evaluate the original instrument.…”
Section: Methodssupporting
confidence: 84%
“…The original developer of the WHQ, and the developers of a revised version of the instrument, used PCA with Varimax rotation to explore the factor structure (Girod, de la, Keininger & Hunter, 2006; Hunter, 2000). Varimax is an orthogonal rotation that minimizes the complexity of the components by increasing large loadings and decreasing small loadings within each component, and it is by far the most commonly used method (Costello & Osborne, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the structure of the WHQ was examined in a UK sample; a revised model was developed and verified to be used in multicenter, international studies 38 . The revised WHQ comprised 23 items, investigating six domains.…”
Section: Women's Health Questionnairementioning
confidence: 99%
“…The following scales are introduced according to their chronological order of construction. They are listed in Table 3 [36][37][38][39][40][41][42][43][44][45] .…”
Section: Assessment Of Health-related Quality Of Life In Aging and CLmentioning
confidence: 99%
“…Health-related quality of life (HR-QoL), which will be measured with the revised version of Women's Health Questionnaire (WHQ23) [43]. This is a specific questionnaire for women in perimenopause, menopause and post menopause stages, that comprises six domains: anxiety/depression, well-being, somatic symptoms, memory/concentration, vasomotor symptoms and sleep problems.…”
Section: Methodsmentioning
confidence: 99%